Effects of empathic and positive communication in healthcare consultations: a systematic review and meta-analysis. (July 2018) - Howick, Jeremy; Moscrop, Andrew; Mebius, Alexander; Fanshawe, Thomas R; Lewith, George; Bishop, Felicity L; Mistiaen, Patriek; Roberts, Nia W; Dieninytė, Eglė; Hu, Xiao-Yang; Aveyard, Paul; Onakpoya, Igho J
Background: Practitioners who enhance how they express empathy and create positive expectations of benefit could improve patient outcomes. However, the evidence in this area has not been recently synthesised. Objective: To estimate the effects of empathy and expectations interventions for any clinical condition. Design: Systematic review and meta-analysis of randomised trials. Data sources: Six databases from inception to August 2017. Study selection: Randomised trials of empathy or expectations interventions in any clinical setting with patients aged 12 years or older. Review methods: Two reviewers independently screened citations, extracted data, assessed risk of bias and graded quality of evidence using GRADE. Random effects model was used for meta-analysis. Results: We identified 28 eligible (n = 6017). In seven trials, empathic consultations improved pain, anxiety and satisfaction by a small amount (standardised mean difference −0.18 [95% confidence interval −0.32 to −0.03]). Twenty-two trials tested the effects of positive expectations. Eighteen of these (n = 2014) reported psychological outcomes (mostly pain) and showed a modest benefit (standardised mean difference −0.43 [95% confidence interval −0.65 to −0.21]); 11 (n = 1790) reported physical outcomes (including bronchial function/ length of hospital stay) and showed a small benefit (standardised mean difference −0.18 [95% confidence interval −0.32 to −0.05]). Within 11 trials (n = 2706) assessing harms, there was no evidence of adverse effects (odds ratio 1.04; 95% confidence interval 0.67 to 1.63). The risk of bias was low. The main limitations were difficulties in blinding and high heterogeneity for some comparisons. Conclusions: Greater practitioner empathy or communication of positive messages can have small patient benefits for a range of clinical conditions, especially pain. Protocol registration: Cochrane Database of Systematic Reviews (protocol) DOI: 10.1002/14651858.CD011934.pub2.